The Cytosolic DNA-Sensing cGAS-STING Pathway in Liver Diseases - Wang, Zhilei; Chen, Nian; Li, Zhiyong; Xu, Guang; Zhan, Xiaoyan; Tang, Jianyuan; Xiao, Xiaohe; Bai, Zhaofang (Frontiers in Cell and Developmental Biology, 2021)
Inflammation is regulated by the host and is a protective response activated by the evolutionarily conserved immune system in response to harmful stimuli, such as dead cells or pathogens. cGAS-STING pathway is a vital natural sensor of host immunity that can defend various tissues and organs against pathogenic infection, metabolic syndrome, cellular stress and cancer metastasis. The potential impact of cGAS-STING pathway in hepatic ischemia reperfusion injury, alcoholic/non-alcoholic steatohepatitis, hepatic B virus infection, and other liver diseases has recently attracted widespread attention. In this review, the relationship between cGAS-STING pathway and the pathophysiological mechanisms and progression of liver diseases is summarized. Additionally, we discuss various pharmacological agonists and antagonists of cGAS-STING signaling as novel therapeutics for the treatment of liver diseases. A detailed understanding of mechanisms and biology of this pathway will lay a foundation for the development and clinical application of therapies for related liver diseases.